“They're Going to Zoom It”: A Qualitative Investigation of Impacts and Coping Strategies During the COVID-19 Pandemic Among Older Adults - Greenwood-Hickman, Mikael Anne; Dahlquist, Jacklyn; Cooper, Julie; Holden, Erika; McClure, Jennifer B.; Mettert, Kayne D.; Perry, Stephen R.; Rosenberg, Dori E. (Frontiers in Public Health, 2021)
Introduction: Older adults, who already have higher levels of social isolation, loneliness, and sedentary behavior, are particularly susceptible to negative impacts from social distancing mandates meant to control the spread of COVID-19. We sought to explore the physical, mental, and social health impacts of the pandemic on older adults and their coping techniques. Materials and Methods: We conducted 25 semi-structured interviews with a sub-sample of participants in an ongoing sedentary behavior reduction intervention. Interviews were recorded and transcribed, and iterative coding was used to extract key themes. Results: Most participants reported an increase in sedentary behavior due to limitations on leaving their home and increased free time to pursue seated hobbies (e.g. reading, knitting, tv). However, many participants also reported increased levels of intentional physical activity and exercise, particularly outdoors or online. Participants also reported high levels of stress and a large decrease in in-person social connection. Virtual connection with others through phone and video was commonly used to stay connected with friends and family, engage in community groups and activities, and cope with stress and social isolation. Maintenance of a positive attitude and perspective gained from past hardships was also an important coping strategy for many participants. Discussion: The COVID-19 pandemic and associated social distancing measures have impacted older adults’ perceived levels of activity, stress, and social isolation, but many leveraged technology and prior life experiences to cope. These themes could inform future interventions for older adults dealing with chronic stress and isolation.